2012
DOI: 10.1111/j.1939-1676.2011.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Disease in Cats Infected with Feline Immunodeficiency Virus

Abstract: Background Feline immunodeficiency virus (FIV) and human immunodeficiency virus (HIV) infection cause similar clinical syndromes of immune dysregulation, opportunistic infections, inflammatory diseases, and neoplasia. Renal disease is the 4th most common cause of death associated with HIV infection. Objective To investigate the association between FIV infection and renal disease in cats. Animals Client‐owned cats (153 FIV‐infected, 306 FIV‐noninfected) and specific‐pathogen‐free (SPF) research colony cats (95 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 22 publications
1
33
2
1
Order By: Relevance
“…Hypotonic fluid losses through vomiting, diarrhea, fever, renal compromise, and decreased water intake can contribute to increased plasma sodium concentrations. Renal diseases are suspected in FIV infection, but a causal association has been difficult to prove . We found no difference between FIV‐infected cats and controls in plasma creatinine concentration, and genitourinary diseases were not a major problem in either group.…”
Section: Discussioncontrasting
confidence: 56%
“…Hypotonic fluid losses through vomiting, diarrhea, fever, renal compromise, and decreased water intake can contribute to increased plasma sodium concentrations. Renal diseases are suspected in FIV infection, but a causal association has been difficult to prove . We found no difference between FIV‐infected cats and controls in plasma creatinine concentration, and genitourinary diseases were not a major problem in either group.…”
Section: Discussioncontrasting
confidence: 56%
“…In a recent study, performed among client-owned cats, no association was detected between FIV infection and renal azotemia was found but 25% (16/64) of naturally FIV-infected cats were proteinuris compared to FIV-uninfected cats (10.3%, 20/195) [20]. Also in our study, only 1/51 experimentally infected animal by FIV-M2, sacrificed one year pi, showed azotemia (serum creatinine 144 µmol/L and mild proteinuria 3.9 g/L with urine protein concentration (UPC) 0.43) (Chronic Renal Failure stage 2) [21].…”
Section: Resultsmentioning
confidence: 99%
“…56 To date epidemiological studies have not been able to substantiate a clinical association between FIV and CKD. 57,58 o Morbillivirus: Several studies have raised interest in a potential association between CKD and morbillivirus infection (FmoPV), a paramyxovirus identified in cats. [59][60][61][62][63] The virus was shown to have cytopathic effects in FCRK cell lines and in small numbers of stray cats there seemed to be a higher prevalence of tubulointerstitial nephritis in the cats that were positive for the feline morbillivirus than in negative cats, although little demographic and phenotypic data was available for either group.…”
Section: Association Of the Development Of Chronic Kidney Disease Witmentioning
confidence: 99%